2005
DOI: 10.1002/masy.200551126
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Process of Binding Between the Anionic Surfactants Sodium Dodecyl Sulfate and Sodium Cholate in Bovine Serum Albumin

Abstract: Summary: In this study sodium cholate (NaC) was used as a representative bile salt for the competitive binding between NaC and sodium dodecyl sulfate (SDS) in bovine serum albumin (BSA), in 0.02 M tris-HCl buffer solution at pH 7.50 and 25 8C. The NaC and SDS associations with BSA were monitored at low surfactant concentrations where only this specific binding process can develop. The applied method to monitor the binding was based on the analysis of the effect of SDS and NaC concentrations and their mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…17,19 Our research group has extensively studied micellar systems formed by the self-assembly of copolymers 20,21 and surfactants. [22][23][24][25] We have investigated a large collection of synthetic polymers and biopolymers, [26][27][28] as well as surfactants and biosurfactants. [27][28][29][30] Interestingly, interactions between water-soluble uncharged polymers and the anionic surfactants have been widely investigated for several decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19 Our research group has extensively studied micellar systems formed by the self-assembly of copolymers 20,21 and surfactants. [22][23][24][25] We have investigated a large collection of synthetic polymers and biopolymers, [26][27][28] as well as surfactants and biosurfactants. [27][28][29][30] Interestingly, interactions between water-soluble uncharged polymers and the anionic surfactants have been widely investigated for several decades.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] We have investigated a large collection of synthetic polymers and biopolymers, [26][27][28] as well as surfactants and biosurfactants. [27][28][29][30] Interestingly, interactions between water-soluble uncharged polymers and the anionic surfactants have been widely investigated for several decades. On the other hand, few studies concerning the interactions of mixtures of bile salts and polyelectrolytes are found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…With proteins such as the BSA, binding studies with this bile salt have previously been performed but only under conditions of very low surfactant concentration were the specific binding process predominates [1,5]. In this context, we have shown that NaC binds specifically to the BSA but, in mixtures with SDS, they compete for the BSA binding site occupancy [10].…”
Section: Introductionmentioning
confidence: 98%
“…We have recently studied the competitive binding process for NaC and SDS with bovine serum albumin at low surfactant concentration in 0.02 M Tris-HCl buffer solution at pH 7.50 [10]. The analyses, based on the average number of surfactant molecules bound to the protein, indicated that SDS is a more efficient quencher than the bile salt.…”
Section: Introductionmentioning
confidence: 99%
“…17 Um sistema bastante estudado é a interação PEO-SDS, onde tem sido mostrado que a cadeia polimérica se envolve ao redor da micela, e que as interações variam de acordo com o tamanho da cadeia do polímero. 5,6,10,13,[18][19][20][21][22][23] Comumente, sistemas formados por polímeros não iônicos e surfactantes iônicos são governados por forças de interação entre grupos hidrofílicos, hidrofóbicos e iônicos. Soluções aquosas de etil(hidroxietil)celulose (EHEC) com adição de um surfactante aniônico constituem um sistema típico desta classe.…”
Section: Introductionunclassified